The measurement and behavior of uncertainty: Evidence from the ECB Survey of Professional Forecasters - Robert Rich; Joseph Song; Joseph Tracy (Federal Reserve Bank of New York, 2012)
We use matched point and density forecasts of output growth and inflation from the ECB Survey of Professional Forecasters to derive measures of forecast uncertainty, forecast dispersion, and forecast accuracy. We construct uncertainty measures from aggregate density functions as well as from individual histograms. The uncertainty measures display countercyclical behavior, and there is evidence of increased uncertainty for output growth and inflation since 2007. The results also indicate that uncertainty displays a very weak relationship with forecast dispersion, corroborating the findings of other recent studies indicating that disagreement is not a valid proxy for uncertainty. In addition, we find no correspondence between movements in uncertainty and predictive accuracy, suggesting that time-varying conditional variance estimates may not provide a reliable proxy for uncertainty. Last, using a regression equation that can be interpreted as a (G)ARCH-M-type model, we find limited evidence of linkages between uncertainty and levels of inflation and output growth.
Keywords: C10; C83; D84; 330; uncertainty; disagreement; inflation expectations; output growth expectations